Gastrointestinal issues in PICU: An unopened chapter - Maninder Singh Dhaliwal; Veena Raghunathan; Mohit Kehar; Moinak Sen Sharma (Wolters Kluwer Medknow Publications, 2016)
Gastrointestinal (GI) problems occur frequently and are often considered to be just a fact of life in pediatric intensive care units; they do not usually get the importance they deserve. This is substantiated by the fact that gastrointestinal function is not included in any of the scoring systems widely used to assess organ failure in critical illness. Defining gastrointestinal failure or dysfunction is complex; however recent attempts have been made to address acute gastrointestinal injury in critical illness. This review addresses the following common GI issues in PICU: constipation, diarrhea, feeding intolerance and stress ulcer prophylaxis.